Digital Footprint Matters: Edukasi Komunikasi untuk Generasi Melek Teknologi Bagi Siswa SMP di Pondok Pesantren Al-Kaffah - Utaminingsih, Sri; Trihandayani, Estiningsih; Sari, Meilani; Khasanah, Salsabila Nurul; Delima, Putri; Putri, Maulida Utami; Feriady, Zainul (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
Rapid digital transformation has brought significant changes to the way people communicate. Over the past two decades, this transformation has drastically altered communication patterns, with social media becoming the primary medium for sharing information, building social interactions, and expressing opinions publicly (Afif et al., 2024). Platforms such as Facebook, Twitter, Instagram, and TikTok enable communication across geographical and cultural boundaries, creating a fast, open, and massive communication space (Mujahiddin & Harahap, 2017). Based on this context, a Community Service Program (PKM) was conducted at Pondok Pesantren Al-Kaffah under the theme “Digital Footprint Matters: Communication Education for a Technology-Literate Generation among Junior High School Students at Pondok Pesantren Al-Kaffah.” The purpose of this program is to train students’ critical thinking skills in addressing and solving digital-related issues among adolescents. The method used in this socialization activity is participatory, educative, and applicative. Through this approach, students are not only expected to understand the material theoretically but also to apply it in their daily lives. Through active collaboration between university students, teachers, boarding school mentors, and students, this program is expected to provide not only short-term benefits in the form of improved digital literacy but also to foster a sustainable positive digital culture within the Pondok Pesantren Al-Kaffah environment.